Determinants of Peroxisome Membrane Dynamics - Carmichael, Ruth E.; Schrader, Michael (Frontiers in Physiology, 2022)
Organelles within the cell are highly dynamic entities, requiring dramatic morphological changes to support their function and maintenance. As a result, organelle membranes are also highly dynamic, adapting to a range of topologies as the organelle changes shape. In particular, peroxisomes – small, ubiquitous organelles involved in lipid metabolism and reactive oxygen species homeostasis – display a striking plasticity, for example during the growth and division process by which they proliferate. During this process, the membrane of an existing peroxisome elongates to form a tubule, which then constricts and ultimately undergoes scission to generate new peroxisomes. Dysfunction of this plasticity leads to diseases with developmental and neurological phenotypes, highlighting the importance of peroxisome dynamics for healthy cell function. What controls the dynamics of peroxisomal membranes, and how this influences the dynamics of the peroxisomes themselves, is just beginning to be understood. In this review, we consider how the composition, biophysical properties, and protein-lipid interactions of peroxisomal membranes impacts on their dynamics, and in turn on the biogenesis and function of peroxisomes. In particular, we focus on the effect of the peroxin PEX11 on the peroxisome membrane, and its function as a major regulator of growth and division. Understanding the roles and regulation of peroxisomal membrane dynamics necessitates a multidisciplinary approach, encompassing knowledge across a range of model species and a number of fields including lipid biochemistry, biophysics and computational biology. Here, we present an integrated overview of our current understanding of the determinants of peroxisome membrane dynamics, and reflect on the outstanding questions still remaining to be solved.